Flora diversity in the Ecuadorian Páramo grassland ecosystem - Fiallos, L.; Herrera, Rafael S.; Velázquez, R. (Cuban Journal of Agricultural Science, 2016)
This research was carried out in the Ecuadorian Páramo grasslands, between 2900 and 4200 m o.s.l, in Loja, Zamora Chinchipe, Azuay, Cañar, Chimborazo, Bolívar, Tungurahua, Cotopaxi, Pichincha, Imbabura and Carchi provinces. For the identification and taxonomical classification of species there were taken herborized samples and identified by agrostologists. The Hitchcock, Gould, Lombardo and Tovar taxonomic keys were used for the identification. From the grasses family, in the eight study places, 90 species were identified, including 37 genus, being the mains, with higher number of species: Festuca (14), Paspalum (10), Agrostis (7), Calamagrostis (7), Bromus (6), Stipa (5), Poa (5), Agropirum (3), Arrhenatherum (2), Brisa (2) and Andropogon (2).The species that prevailed in the study places were: Agrostis breviculmis, Agrostis exigua, Bromus lanatus, Calamagrostis tarmensis, Festuca humilior, Festuca ortophylla, Festuca weberbaueri and Paspalum bomplandianum. The diversity indexes of the existent meadow species showed values from mean (0.72) to high (0.90), as for their uniformity. This allowed determining that the biodiversity is variable, according to the environmental conditions of the studied Páramo grassland ecosystems. Similar performance was obtained for trees grasses species. Key words: Páramo grasslands, Ecuador, grasses, diversity